Problem based learning (PBL) in medical education to facilitate student learning - Kasarla, Rajeshwar Reddy; Choudhary, Sidhya; Khatoon, Naziya; Pathak, Laxmi (Janaki Medical College Journal of Medical Science, 2023)
Life-long learning and the demand for continuous development of skills, knowledge, and attitudes needed in working life have resulted in a call for new ways to organize learning. The knowledge gained in education becomes quickly outdated and loses its value in real-life scenarios. The skills and knowledge needed in working life cannot all be taught during formal schooling and training. Working life requires multidimensional professional skills with a problem-solving approach and abilities for continuous learning via independent knowledge acquisition and its practical application. Problem-based learning is considered an instructional approach that may solve some of the important issues of medical education, such as the difficulties encountered by students in using the knowledge gained in a clinical setting. Problem-based learning (PBL) courses start with the problems rather than with the exposition of disciplinary knowledge, so that medical students are trained to deal with difficult situations in the future, preparing themselves to become active, independent learners and problem solvers, rather than more or less passive recipients of information. This review is undertaken with an objective to describe innovative problem-based learning and teaching concepts to help facilitate the better learning of real life situations in the classroom and enhance critical thinking among medical students